1994
DOI: 10.1073/pnas.91.26.12892
|View full text |Cite
|
Sign up to set email alerts
|

A second class I ribonucleotide reductase in Enterobacteriaceae: characterization of the Salmonella typhimurium enzyme.

Abstract: The nrdA and nrdB genes of Escherichia coli and Salmonella typhimurium encode the Rl and R2 proteins that together form an active class I ribonucleotide reductase. Both organisms contain two additional chromosomal genes, nrdE and nrdF, whose corresponding protein sequences show some homology to the products of the genes nrdA and nrdB. When present on a plasmid, nrdE and nrdF together complement mutations in nrdA or nrdB. We have now obtained in nearly homogeneous form the two proteins encoded by the S.typhimur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
139
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(145 citation statements)
references
References 18 publications
5
139
1
Order By: Relevance
“…Our recent studies of B. subtilis class Ib RNR showed that dATP inhibits RNR activity at concentrations Ͼ5 M (47). This result was surprising because class Ib RNRs do not have an ATP cone or activity domain, the typical binding site for dATP that facilitates class Ia RNR inhibition (52,60,61). To determine whether the S. sanguinis class Ib RNR is inhibited by dATP, the activity of Mn Y ⅐ -NrdF was measured in the presence of increasing dATP concentrations (Fig.…”
Section: Identification Of the Genes For Cluster Assembly And Activitmentioning
confidence: 87%
“…Our recent studies of B. subtilis class Ib RNR showed that dATP inhibits RNR activity at concentrations Ͼ5 M (47). This result was surprising because class Ib RNRs do not have an ATP cone or activity domain, the typical binding site for dATP that facilitates class Ia RNR inhibition (52,60,61). To determine whether the S. sanguinis class Ib RNR is inhibited by dATP, the activity of Mn Y ⅐ -NrdF was measured in the presence of increasing dATP concentrations (Fig.…”
Section: Identification Of the Genes For Cluster Assembly And Activitmentioning
confidence: 87%
“…Repeated trials failed to generate any authentic mutants implying that deletion of both genes is lethal and that S. coelicolor does not possess any other functional RNR systems (indeed, no other genes encoding RNR-like proteins are present in the complete genome sequences of S. coelicolor and Streptomyces avermitilis ). Correlation of this conclusion was obtained from a study of the effect of hydroxyurea -a potent inhibitor of class I RNRs (Sinha and Snustad, 1972;Jordan et al ., 1994) -on the growth of M145 and the nrdB and nrdJ deletion mutant strains. Figure 2 shows that all three strains, M145, M145 D nrdB::apr and M145 D nrdJ::apr , grew equally well on solid medium whereas the M145 D nrdJ::apr strain alone failed to grow in the presence of 10 mM hydroxyurea.…”
Section: A Functional Class Ia or Class II Rnr Is Sufficient For S Cmentioning
confidence: 99%
“…coli NrdE and NrdF have not been previously purified, although the equivalent proteins from Salmonella typhimurium, sharing 89 and 87% sequence identity, respectively, have been purified (10) and their structures have been determined (11,12). Efforts to purify NrdI have been reported but were hampered by poor solubility.…”
mentioning
confidence: 99%